2020
DOI: 10.1093/infdis/jiaa295
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Necroptosis to Prevent Long-term Cardiac Damage During Pneumococcal Pneumonia and Invasive Disease

Abstract: Background Streptococcus pneumoniae infection can result in bacteremia with devastating consequences including heart damage. Necroptosis is a proinflammatory form of cell death instigated by pore-forming toxins such as S. pneumoniae pneumolysin. Necroptosis-inhibiting drugs may lessen organ damage during invasive pneumococcal disease (IPD). Methods In vitro experiments were carried out with human and mouse cardiomyocytes. Lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…For decades, extensive evidence has implicated risk of myocardial infarction in various infectious diseases such as influenza, pneumococcal pneumonia, and bacteremia ( 1 3 ). Our group has previously shown that the bacterium Streptococcus pneumoniae (pneumococcus) is capable of myocardial invasion, induction of cardiomyocyte death, and disruption of cardiac contractility and function during acute infection and convalescence ( 4 6 ). Cardiac complications have also been observed during influenza epidemics and pandemics.…”
Section: Observationmentioning
confidence: 99%
See 1 more Smart Citation
“…For decades, extensive evidence has implicated risk of myocardial infarction in various infectious diseases such as influenza, pneumococcal pneumonia, and bacteremia ( 1 3 ). Our group has previously shown that the bacterium Streptococcus pneumoniae (pneumococcus) is capable of myocardial invasion, induction of cardiomyocyte death, and disruption of cardiac contractility and function during acute infection and convalescence ( 4 6 ). Cardiac complications have also been observed during influenza epidemics and pandemics.…”
Section: Observationmentioning
confidence: 99%
“…Mice were then challenged with S. pneumoniae (strain TIGR4) at a dose of 1 × 10 3 CFU for 2 days before euthanasia. Immunofluorescent staining against S. pneumoniae showed cardiac microlesion ( 4 ) formation only in animals preinfected with IAV ( Fig. 1A ), with a significant increase in the percentage of area of heart with lesions ( Fig.…”
Section: Observationmentioning
confidence: 99%
“…To investigate the importance of necroptosis in cardiomyocyte death and heart injury in sepsis, a number of studies both in vivo and in vitro have been performed ( 53 , 54 ). Beno et al ( 55 ) reported that cardiomyocyte death and heart damage are necroptosis-dependent in a Streptococcus pneumoniae mouse model in which necroptosis inhibition attenuated myocardial injury. The promotive effects of necroptosis on sepsis-associated myocardial damage have been confirmed by cell experiments ( 56 , 57 ).…”
Section: Inflammation and Cardiomyocyte Death In Sepsismentioning
confidence: 99%
“…Very recently, Beno et al using high-resolution echocardiography, observed that administration of ponatinib, a novel multi-tyrosine kinase inhibitor that attenuates necroptosis, to mice with experimentally induced severe pneumococcal disease, resulted in significant attenuation of long-term cardiac damage ( 185 , 186 ). Although these cardio-protective effects of ponatinib were attributed to attenuation of pneumolysin-mediated cardiomyocyte necroptosis, it is also noteworthy that toxin-induced platelet activation and resultant microvascular occlusion represents an additional cause of cardiac necroptosis.…”
Section: Platelet-targeted Adjunctive Strategies In Capmentioning
confidence: 99%